The association between influenza vaccination and the perception of COVID-19 as well as COVID-19 vaccination behavior among community residents in Anhui province, China - Mengjie Guo; Jian’an Li; Yan Wang; Guimei Chen; Ren Chen; Li Wang (Human Vaccines & Immunotherapeutics)
Influenza is a significant public health threat associated with high morbidity and mortality globally. This study investigated the influenza vaccination rate (IVR) among community residents in Anhui province, China, and explored the association between participants’ influenza vaccination and their key sociodemographic characteristics, perception of COVID-19 as well as COVID-19 vaccination behavior. We found that the IVR among respondents in Anhui province was 27.85% in 2020. Regression analyses revealed that males (OR = 1.41, 95% CI: 1.01 ~ 1.96), residents with above middle school education (OR = 1.88, 95% CI: 1.04 ~ 3.39), considered themselves likely to be infected with COVID-19 (OR = 1.53, 95% CI: 1.04 ~ 2.24), had received the COVID-19 vaccine (OR = 9.85, 95% CI: 3.49 ~ 27.78), did not plan to receive COVID-19 vaccine in the future (OR = 1.70, 95% CI: 1.17 ~ 2.47), and had no adverse reactions after COVID-19 vaccination (OR = 1.54, 95% CI: 1.04 ~ 2.27) were associated with a higher IVR. The acceptance of influenza vaccination was mainly associated with respondents’ gender, education, perception of COVID-19, history of COVID-19 vaccination in city and countryside community residents in Anhui province.